(untitled) (Canadian Medical Education Journal, 2020)
We created a clinical ultrasound (CUS) elective in clerkship, which gave medical students the opportunity to enhance their knowledge and technical skills while refining their CUS-related clinical decision making. This elective uniquely allowed medical students to integrate their CUS knowledge and skills into real patient care within the clinical environment (discipline) of their choice. As such, beyond supporting increasing technical competence, students learned to advocate for appropriate use of CUS, an important skill for trainees to develop.